VALIDATION OF QUALITY OF LIFE AND STIGMA QUESTIONNAIRES IN POST-TB BANJAR POPULATION - Juwita Ramadhani; Dyah Aryani Perwitasari; Haafizah Dania (AL ULUM: JURNAL SAINS DAN TEKNOLOGI, 2026)
Tuberculosis (TB) remains a major public health problem with persistent consequences beyond microbiological cure. Post-TB individuals frequently experience impaired health-related quality of life and social stigma influenced by sociocultural context. Among the Ethnic Banjar population in Indonesia, culturally validated instruments for assessing these outcomes remain limited. This study aimed to evaluate the validity and reliability of the HRQ-6D and Van Rie TB Stigma Scale for post-TB populations of Ethnic Banjar. A cross-sectional psychometric study was conducted among 134 respondents (67 post-TB patients and 67 community members). Construct validity was assessed using item–total correlations, Kaiser–Meyer–Olkin (KMO), and Bartlett’s test of sphericity. Internal consistency was evaluated using Cronbach’s alpha. All HRQ-6D items were valid (r=0.284–0.832; α=0.935). The stigma scale demonstrated acceptable validity, except one item, with strong reliability (α=0.927 patients; 0.843 community). Both instruments are valid and reliable for assessing HRQoL and stigma in post-TB Ethnic Banjar populations.